Theoretical and NMR Conformational Studies of β-Proline Oligopeptides With Alternating Chirality of Pyrrolidine Units - Mantsyzov, Alexey B.; Savelyev, Oleg Y.; Ivantcova, Polina M.; Bräse, Stefan; Kudryavtsev, Konstantin V.; Polshakov, Vladimir I. (Frontiers in Chemistry, 2018)
Synthetic β‐peptides are potential functional mimetics of native α-proteins. A recently developed, novel, synthetic approach provides an effective route to the broad group of β‐proline oligomers with alternating patterns of stereogenic centers. Conformation of the pyrrolidine ring, Z/E isomerism of β‐peptide bonds, and hindered rotation of the neighboring monomers determine the spatial structure of this group of β‐proline oligopeptides. Preferences in structural organization and corresponding thermodynamic properties are determined by NMR spectroscopy, restrained molecular dynamics and quantum mechanics. The studied β‐proline oligopeptides exist in dimethyl sulfoxide solution in a limited number of conformers, with compatible energy of formation and different spatial organization. In the β‐proline tetrapeptide with alternating chirality of composing pyrrolidine units, one of three peptide bonds may exist in an E configuration. For the alternating β‐proline pentapeptide, the presence of an E configuration for at least of one β‐peptide bond is mandatory. In this case, three peptide bonds synchronously change their configurations. Larger polypeptides may only exist in the presence of several E configurations of β‐peptide bonds forming a wave-like extended structure.